Pécs iparának változásai az 1950-es években - Kaposi, Zoltán (Közép-Európai Közlemények, 2013)
This study deals with the industrialisation of the fifth biggest Hungarian city, Pécs. It was the largest city of South Transdanubia, in 1949 Pécs had 84 000 citizens. The basic question of the study is what kind of structural changes occurred in the industry of the city during the First Five-Year Plan (1950–54) period. Pécs was an industrial city before 1945. The new communist economic policy supported the large-scale industry. Two heavy industry companies developed rapidly: the colliery and the uranium mine. These two together gave 60% of the employment in the industrial sector of the city. Meanwhile the leather-work and the china industry were stiltedly developed. In order to improve local supply, city council managed medium-scale factories were established which mainly provided services. Former private artisans were forced to enter to small-scaled cooperatives or to become employees of large-scale factories. The privately owned small-scale industry had a 20% before the World War II -it decreased to 5%. In the first decade of the planned economy the industry of Pécs became very deformed. Changes came only in the second half of the 1960s.